The Effect of Nitrogen Concentration on Compatible Solutes During Salinity Stress in Thellungiella salsuginea - Tattersall, Ashley (My University, 2009)
Thellungiella salsuginea, a crucifer relative of Arabidopsis thalinana, tolerates extreme abiotic stresses such as salt, drought and cold (Taji et al., 2004; Inan et al., 2004; Gong et al., 2005 ; Wong et al. , 2006; Griffith et al. , 2007). Investigations into the abiotic stress tolerance of this plant have shown that the accumulation of compatible solutes in the cytosol of the cell can help restore cellular osmotic balance during periods of osmotic stress (Flowers et al. , 1977; Greenway and Munns, 1980; Hasegawa and Bressan, 2000). The objective of this study was to identify qualitative and quantitative changes in polar metabolites present in T. salsuginea seedlings subjected to saline conditions. Seeds were germinated on Murashige and Skoog media and then T. salsuginea seedlings were transferred to defined tissue culture media where they were grown for a period of one to two weeks in the presence or absence of 100 mM NaCI (-S/+S) and under conditions of 0.1 mM or 1.0 mM nitrogen (designated LN and HN for low and high nitrogen, respectively). Shoot and root biomass and length determinations were taken daily and shoot tissue was extracted for analysis of polar metabolites by gas chromatography/mass spectrometry (GC/MS). Our hypothesis was that T. salsuginea seedlings experiencing salt stress would accumulate compatible solutes and that the level of nitrogen in the growing medium would have no influence on that outcome. Among the mass spectral tags (MSTs), proline has been proposed to perform the functions of a compatible solute (Hare et al. , 1998; Zhu et al. , 2001). If proline is a compatible solute in salinized plants we might expect the proline content to be the same and independent of nitrogen availability or that plants with low proline would perform poorly. However, we found the proline content in salinized plants on LN to be 6.3-fold lower than in seedlings on HN+S media and root elongation and shoot biomass were not affected in seedlings on LN+S media relative to controls.
T. salsuginea grown under HN+S or LN+S grew at the same rate (average of 2.2 mm•d-1 ) and showed a 50% reduction in primary root elongation rate compared to HN or LN controls. As such, the presence of salt slowed the rate of root elongation but the level of N present had no effect. At the time of harvest, which averaged 18.7 ± 2.1 d for +S seedlings and 8.7 ± 1.5 d for -S seedlings, shoot fresh weight for plants on HN+S and LN+S media did not significantly differ from their respective controls. GC/MS analysis of metabolites showed that 49 MSTs underwent statistically significant (p <= 0.05) changes for the four treatment combinations. Of these, the metabolites proline, raffinose, fructose and myo-Inositol were found by principal component analysis (PCA) to contribute strongly to the separation among treatment-specific datasets.
GC/MS datasets from HN, LN, HN+S, LN+S seedlings were compared with comparable datasets from mature, cabinet-grown plants (control unsalinized; C-0) and plants irrigated with solutions containing 300 mM NaCl (salinized; S-300) and mature field plants harvested over three growing seasons at a Yukon field site (2003 , 2005 and 2006). In this meta-analysis, metabolic profiles were analyzed using ANOVA and of the ca. 300 metabolic compounds detected, only 52 underwent changes in abundance deemed statistically significant (p <= 0.05). PCA and hierarchal cluster analysis (HCA) showed that metabolite profiles from HN, LN and C-0 were most similar to each other and metabolite profiles of HN+S seedlings more closely resembled S-300 plants. Metabolite profiles of leaves from field plants harvested in 2005 and 2006 were similar to those of seedlings exposed to LN+S while those from 2003 were very distinct from other datasets.
PCA identified proline as an MST strongly contributing to the placement of S-300 and HN+S datasets, while 2005 and 2006 field plants and LN+S plants accumulated carbohydrates, such as raffinose, fructose and several unidentifiable sugars but not proline. These results suggest that accumulation of carbohydrates may be an important stress tolerance strategy of T. salsuginea grown under field conditions whereas proline may be a compatible solute when nitrogen is not limiting.
Our study shows that T. salsuginea displays metabolic plasticity with respect to the organic solutes accumulated under osmotic stress and that nitrogen availability can influences the composition of accumulated organic solutes in seedlings grown on defined media. We propose that this plasticity may operate in the field where nitrogen content of soils is low and proline content of plants is as well. This plasticity may contribute towards T. salsuginea's exceptional ability to survive and even thrive in extreme environments.
Keywords: Biology; Biology